Integration of Artificial Intelligence in Digital Marketing Strategies Based on Business Data Analytics: Integrasi Kecerdasan Buatan dalam Strategi Pemasaran Digital Berbasis Analisis Data Bisnis - Aini, Qurotul; Dyatmika, Sutama Wisnu; Chakim, Mochamad Heru Riza; Khasanah, Miftakhul; Queen, Zabenaso (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
The digital transformation in the era of Artificial Intelligence (AI) has revolutionized marketing practices by placing data analysis at the core of adaptive and precision-based strategies. This study aims to analyze how the integration of AI and business data analytics can strategically and sustainably enhance the effectiveness of digital marketing. The research method employs a qualitative approach through literature review and case analysis of AI implementation in digital business contexts. The findings indicate that the use of AI in market segmentation, consumer behavior prediction, and content personalization significantly improves conversion rates, customer loyalty, and marketing cost efficiency. Moreover, this technological integration also supports the achievement of the Sustainable Development Goals (SDGs), particularly Goal 8 (decent work and economic growth) and Goal 9 (industry, innovation, and infrastructure). These findings highlight the importance of strengthening digital capabilities through the adoption of AI-based technology and data analytics as a foundation for building responsive, innovative, and sustainable marketing strategies aligned with the demands of the digital economy.